Advances and recent trends in plant-based materials and edible films: a mini-review - Olawade, David B.; Wada, Ojima Z.; Ige, Abimbola O. (Frontiers in Chemistry, 2024)
Plant-based materials and edible films have emerged as promising alternatives to conventional packaging materials, offering sustainable and environmentally friendly solutions. This mini-review highlights the significance of plant-based materials derived from polysaccharides, proteins, and lipids, showcasing their renewable and biodegradable nature. The properties of edible films, including mechanical strength, barrier properties, optical characteristics, thermal stability, and shelf-life extension, are explored, showcasing their suitability for food packaging and other applications. Moreover, the application of 3D printing technology allows for customized designs and complex geometries, paving the way for personalized nutrition. Functionalization strategies, such as active and intelligent packaging, incorporation of bioactive compounds, and antimicrobial properties, are also discussed, offering additional functionalities and benefits. Challenges and future directions are identified, emphasizing the importance of sustainability, scalability, regulation, and performance optimization. The potential impact of plant-based materials and edible films is highlighted, ranging from reducing reliance on fossil fuels to mitigating plastic waste and promoting a circular economy. In conclusion, plant-based materials and edible films hold great potential in revolutionizing the packaging industry, offering sustainable alternatives to conventional materials. Embracing these innovations will contribute to reducing plastic waste, promoting a circular economy, and creating a sustainable and resilient planet.